Internal versus external CEO choice and the structure of compensation contracts - Palomino, Frédéric; Peyrache, Eloïc (Journal of Financial and Quantitative Analysis, 2013)
Abstract Any firm choosing a chief executive officer (CEO) faces a double problem: candidate selection and choice of a compensation scheme. We derive sufficient conditions where the unique optimal compensation scheme is a capped-bonus contract in a pure moral-hazard environment, while equity is used when the firm also faces adverse selection. Then, we provide a rationale for the simultaneous increases in CEO pay, use of equity in compensation, and external hiring of CEOs. Our results are consistent with empirical evidence that shows externally hired CEOs earn more than those internally hired and that externally hired CEOs get a higher fraction of their compensation equity based.